Influence of temporal changes in climate variables on crop production in South-North Saurashtra zones of Gujarat, India - SK, CHHODAVADIA; MC, CHOPADA; VB, BHALU (Innovare Journal of Agricultural Sciences, 2016)
Climate variability and changes have been implicated to have significant impact on global and regional food production particularly the common stable crops performance in south-north Saurashtra zone of Gujarat. However, the extent and nature of these impact still remain uncertain. In this study, records of crop yield and some climatic variables for a period of 27 years (1988-2014) were used to carry out a comprehensive study of the impact of climate variability on some common classes of food crops in south-north zones of Gujarat with view to determining their responses to observed varying climatic condition. Crops differed markedly in their responses to the climate variables. Mean temperature varied with the crop production compared with other food crops. Production of food crops was largely dependent on the seasonal and inter-annual changes in rainfall. However, combination of a number of interacting factors with both climatic and non-climatic components were responsible for the relatively low coefficient of correlation (r<0.4) between rainfall and crop yield. The climate projections for South-North zone of Gujarat by 2025 would have direct and adverse impacts on food production, distribution, and infrastructure and livelihood assets in Gujarat. Key words: Climate variability, crop yield and production, regional projection, South-North Saurashtra, Gujarat